Integrated Approaches to Combat Cyber-Crime on Social Media: Legislative, Educational, and Technological Solutions - AGBAKA, Joyce (PERSPEKTIF, 2024)
The rapid growth of social media has transformed communication, offering numerous advantages like enhanced connectivity and swift information exchange. However, it has also introduced complex challenges, particularly concerning cybercrime, including identity theft, cyberbullying, online fraud, and misinformation. This paper employs a literature review approach to examine solutions to social media-related cyber crimes. The study synthesizes existing research and identifies four main areas of intervention: comprehensive legislative frameworks to regulate online activities, digital literacy programs to equip users with knowledge on recognizing and responding to cyber threats, technological advancements for detecting and preventing cyber crimes, and strengthened collaboration between private companies and government agencies. Findings suggest that an integrated approach involving legal measures, education, technology, and cross-sector partnerships is essential to create a safer online environment. This study contributes to a broader understanding of how existing frameworks can be enhanced to address the complex nature of cybercrime on social media platforms.